Analysis of a case of pilomatricoma in an adolescent after receiving recombinant hepatitis B vaccine (CHO cell) in Beijing of China - Li Li; Jingyi Xu; Dongkun Zhang; Jianlin Cai; Zhen Li; Xiaohui Zhang; Shuping Li (Human Vaccines & Immunotherapeutics)
We report and analyze a case of pilomatricoma in an adolescent after receiving recombinant hepatitis B vaccine (CHO cell) in Chaoyang District of Beijing and to evaluate the causality between the disease and vaccination. Based on the professional branch of this case, we organized a seminar and we invited specialists in vaccinology, epidemiology, dermatology, infectiology, and immunology to participate in the conference. Specialists evaluated the relevance and causality between the vaccination and disease. The clinical diagnosis of the adolescent was pilomatricoma after receiving recombinant hepatitis B vaccine (CHO cell) which could not be disregarded as an adverse reaction following immunization. Although rare, there is a possibility of developing pilomatricoma after vaccination. This suggests that the implementation process of vaccination should be standardized and that the injection site after vaccination should be nursed properly.